Satisfaction Among RNs With Anesthetic Services at Srinagarind Hospital - Sabangban, Lumyai; Chau- In, Waraporn; Sumret, Krisana; Thinsheelong, Wiriya; Malasai, Pikool (Srinagarind Medical Journal, 2013)
Abstract Object : To assess the level of satisfaction among all registered nurses (RNs)(excluding anesthetic nurses) with the provision of ansesthetic service at Srinagarind Hospital, Knonkaen University, Thailand. Materials and Methods : Using purposive sampling, we selected 200 RNs (not anesthetic nurses) from all wards at Srinagarind Hospital. Questionnaires comprised three parts : Part 1 – demographics and work place; Part 2 – level of satisfaction among ward RNs vis-a-vis the provision of anesthetic service, c) knowledge, and d) personnel; and Part 3 – open-ended questions). Results : The reliability of the survey was 0.92. The data were analyzed and presented as percentages, means and standard deviations. The satisfaction among RNs from all of the wards vis-avis the provision of anesthetic service was high, namely: a) administration 2.72 ±0.50; b) service 3.30±0.46;c) knowledge 2.90±0.45; and , c) personnel 3.22 ±0.46. The open-ended questions indicated that RNs expected better communications and relationships amongst all of the members of the anesthetic team. They felt that the distribution of knowledge about anesthesiology was inadequate and would like to be better informed before serving with postoperative patients. Conclusion: Overall RN-satisfaction with anesthetic service in all wards was high (3.03±0.36). RNs valued good communications among the whole team and would like to be better informed about each patient’s anesthesiology needs. In so doing,the RNs believed the delivery of anesthetic services would improve. Keywords: Vitamin D Deficiency; Calcidiol; PTH; Postmenopausal Women